1,1′-(Propane-1,3-diyl)bis(3-phenylurea) - Pansuriya, Pramod (International Union of Crystallography, 2011)
The title compound, C(17)H(20)N(4)O(2), has crystallographic inversion symmetry. In the crystal structure, intermolecular hydrogen bonding between adjacent urea groups gives rise to infinite polymeric chains diagonally across the bc plane. With a centroid–centroid distance of 3.295 (2) Å, π–π stacking is present in the crystal along the same plane.